INFORMAL LABOR RELATIONS WITHIN THE INDUSTRIAL ENTERPRISES OF THE LATE RUSSIAN EMPIRE (City: History, Culture, Society, 2018)
The article presents a study of informal labour relations within the industrial enterprises of the Russian Empire based on materials from the Dnieper-Donets region during the period 1870–1917. The analysis is based on narrative writings created by the entrepreneurs and workers as primary sources, supplemented by analytical data collected by the zemstvo and state commissions.The article demonstrates that informal labour relations took various forms such as informal employment, manipulation with the workers’ wages, requiring and performing activates which were not listed in the employment contract, and corruption. The combination of mutual benefits and risks for the main stakeholders determined the system of informal labour relations. The omnipresence of these informal practices was due to the ignorance of both the employees and the employers concerning the relevant legislation. Inefficient state control over labour law also contributed to the expansion of informal institutions.During the last quarter of the nineteenth and early twentieth century, formal practices dislodged some informal variations. It happened due to the modernization of the work ethic on both the workers’ and the industrialists’ side, the strengthening of the regulatory and controlling role of the state, and, most importantly, the organizational changes within the industrial enterprises. The rise of large modern industrial enterprises with a hierarchy of salaried managers demanded a system of new, more formal labour relations between the employers and employees. However, the formalization of labour relations in the industrial enterprises in Russia was not a linear process. Some informal practices proved to be very viable and have survived to-date.
Keywords: informal labor relations; informal economy; informal employment; the Donbas; Late Russian Empire